Evolutionary relationships within the Phytophthora cactorum species complex in Europe. Issue 6 (June 2016) - Pánek, Matěj; Fér, Tomáš; Mráček, Jaroslav; Tomšovský, Michal
Abstract: The Phytophthora cactorum species complex in Europe is composed of P. cactorum, Phytophthora hedraiandra, and a hybrid species Phytophthora × serendipita . Evolutionary analyses using the amplified fragment length polymorphism (AFLP) method were carried out on 133 isolates from 19 countries. The AFLP data were complemented by sequence analysis of three genes (ITS region of ribosomal RNA gene, phenolic acid decarboxylase – Pheca I, and Cytochrome oxidase – Cox I), morphometric analysis and cardinal temperature data. The high proportion of clonal genotypes, low gene flow among groups, which was defined by the structure analysis, and low Nei's gene diversity confirms the homothallic life cycle of the groups. On the other hand, the ITS, Cox I and Pheca I sequence data support occasional hybridization between species. The structure K = 5 grouping revealed two groups of hybrid origin (C2 and F). While the C2 group resembles P . × serendipita, the F group includes Finnish isolates characterized by high oogonial abortion rates and slow growth. The morphological characters routinely used in identification of Phytophthora species are not useful for delimitation of species from the P. cactorum complex. Therefore, we discuss the status of P. hedraiandra as a separate species. The epitypification of P. cactorum is proposed. Highlights: Phytophthora cactorum species complex is created by at least five genetic lineages. Phytophthora hedraiandra is one of P. cactorum lineages originating probably from Europe. P. cactorum lineages occasionally hybridize despite of homothallic nature. Phytophthora × serendipita is one of more intraspecific hybrids within the complex. Only Phytophthora cactorum sensu stricto hybridizes with Phytophthora nicotianae.